Connecting the dots: Knowledge management as mediator and moderator between intellectual capital and procurement performance - Cahyo, Septian Dwi; Zulbainarni, Nimmi; Taryana, Asep (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
Knowledge management is increasingly regarded as a strategic element in the public sector due to its potential in managing intangible assets such as intellectual capital. This study aims to examine the role of knowledge management as both a mediating and moderating variable in the relationship between public intellectual capital and government procurement performance, with a case study at the Ministry of Finance. Public intellectual capital is divided into five components: human capital, organizational capital, social capital, technological capital, and relational capital. The analysis employs structural equation modeling – partial least squares (SEM-PLS) with a total of 298 respondents. In the first model, where knowledge management is positioned as a moderating variable, the results indicate that human, social, and relational capital have a significant direct impact on procurement performance. However, knowledge management does not demonstrate a significant moderating effect on these relationships. In contrast, the second model highlights the mediating role of knowledge management, which significantly bridges the influence of several intellectual capital components, specifically organizational, social, technological, and relational capital on procurement performance outcomes. This study underscores the theoretical relevance of positioning knowledge management as a mediating mechanism in public intellectual capital research. These findings further emphasize the importance of systematically and strategically integrating knowledge management into intellectual capital, rather than merely as a supporting factor.